Design and Implementation of Anti-Theft Distribution Transformer Monitoring System for Rural Africa - Okandeji, Alexander Akpofure; Onaifo, Frank; Alao, Peter Olufemi; Ojo, Stephen; Okunfolarin, Oladimeji (IPTEK The Journal for Technology and Science, 2023)
This paper designs a 15KVA three-phase distribution transformer incorporated with a three-phase smart meter for automatic monitoring against theft and vandalism. The monitoring system is designed to send short message services (SMS) to the power utility company when there are abnormalities in the transformer parameters [such as overload, temperature rise, load current, oil level, and voltage variation]. The monitoring unit consist of an embedded system which houses the Arduino Microcontroller, global system for mobile communication (GSM) modem SIM900 for sending SMS, load current sensors which determines the load connected to the transformer, and Bypass current sensors which checks for illegal connection to the transformer. The Arduino Microcontroller/embedded system is connected through a relay to the distribution transformer while the SIM900/GSM module is connected to the Microcontroller/embedded system, relay and optocoupler. The optocoupler isolates the high voltage side of the circuit from the low voltage side. The embedded module process, transmit and receive the parameters to/ from the GSM modem while the GSM module is the link between the embedded system and the public GSM network. The utility provider is expected to have a personal computer (PC)-based -server located at the utility control center basically to collect data from the transformer. This paper presents an alternative method of protecting transformer electrical installations using electronic means compared to the conventional cases of using patrol vehicles by the power utility service provider.